Sustainable fisheries certification process in the developing countries : potential of tourism industry in the Philippines - Lähteenkorva, Maija (2017)
This thesis focuses on looking at market-driven approach to establishing sustainable fisheries in developing countries. Market-driven approaches consist of sustainable fisheries certification or also known as ecolabels that are based on economic incentives. The aim of this study is to identify potential certification processes suitable for the Philippines tourism industry. The study first identified criteria for sustainable fisheries certification, which was done using Marine Stewardship Council (MSC) standards. Second part of the study conducted a market analysis on selected local resorts, looking at their current seafood sustainability and focusing especially on whether there is any demand for sustainable seafood supplier.